COSMIC: the Catalogue Of Somatic Mutations In Cancer. Issue Volume 47:Issue D1(2019) (29th October 2018) - Tate, John G; Bamford, Sally; Jubb, Harry C; Sondka, Zbyslaw; Beare, David M; Bindal, Nidhi; Boutselakis, Harry; Cole, Charlotte G; Creatore, Celestino; Dawson, Elisabeth; Fish, Peter; Harsha, Bhavana; et al.
Abstract: COSMIC, the Catalogue Of Somatic Mutations In Cancer (https://cancer.sanger.ac.uk ) is the most detailed and comprehensive resource for exploring the effect of somatic mutations in human cancer. The latest release, COSMIC v86 (August 2018), includes almost 6 million coding mutations across 1.4 million tumour samples, curated from over 26 000 publications. In addition to coding mutations, COSMIC covers all the genetic mechanisms by which somatic mutations promote cancer, including non-coding mutations, gene fusions, copy-number variants and drug-resistance mutations. COSMIC is primarily hand-curated, ensuring quality, accuracy and descriptive data capture. Building on our manual curation processes, we are introducing new initiatives that allow us to prioritize key genes and diseases, and to react more quickly and comprehensively to new findings in the literature. Alongside improvements to the public website and data-download systems, new functionality in COSMIC-3D allows exploration of mutations within three-dimensional protein structures, their protein structural and functional impacts, and implications for druggability. In parallel with COSMIC's deep and broad variant coverage, the Cancer Gene Census (CGC) describes a curated catalogue of genes driving every form of human cancer. Currently describing 719 genes, the CGC has recently introduced functional descriptions of how each gene drives disease, summarized into the 10 cancer Hallmarks.